Hepatic encephalopathy aggravated by systemic inflammation - Manzhalii, Elina; Stremmel, Wolfgang (Digestive diseases, 2019)
Background: The pathogenesis of hepatic encephalopathy (HE) is only partially understood. Beside ammonia accumulation in brain, a proinflammatory component has been suggested as precipitating event. Objectives: To evaluate the role of cytokines in cirrhosis for development of HE. Methods: Pro- and anti-inflammatory cytokine profiles were determined in rats with CCL4-induced cirrhosis and HE as well as in patients with cirrhosis either due to metabolic disorders or chronic hepatitis C virus (HCV) with various grades of concomitant HE and depression. Results: In the rat model and human cirrhosis a proinflammatory cytokine pattern (elevation of interferon gamma, interleukin [IL]-1β, IL-6) was registered which in humans correlated to the degree of HE and depression. The most prominent elevation of proinflammatory cytokines was observed in chronic HCV as an additional inflammatory stimulus. In all cases of cirrhosis a comparable background activation of anti-inflammatory cytokines (e.g., IL-4) was detected which was interpreted as a physiologic counterbalance mechanism. Conclusions: The degree of HE and depression correlated with a proinflammatory cytokine pattern. It suggests that beside ammonia elevation, inflammatory cytokines determine occurrence and severity of hepatic encephalopathies. Thus, it can be defined a preferential therapeutic target.